COMPARATIVE GC–MS CHARACTERIZATION AND PHYSICOCHEMICAL EVALUATION OF Citrus hystrix DC. ESSENTIAL OILS FROM DIFFERENT PLANT PARTS - Ramadhan, Dwi Sapri; Warsito, Warsito; Azzahra, Vina Octavia; Wardana, Dian; Fahmi, Jam’an; Safitri, Wulan Dwi (Walisongo Journal of Chemistry, 2025)
Essential oils from Citrus hystrix DC. are known for their rich bioactive composition, particularly citronellal, which has extensive applications in the fragrance and pharmaceutical industries. However, comparative studies on the chemical and physicochemical properties of oils extracted from different plant parts remain limited. This study investigated essential oils obtained by steam distillation from leaves (LEO), twigs (TEO), and a leaf–twig mixture (LTMEO). The oils were characterized using GC–MS and FTIR analyses, alongside measurements of density, refractive index, and yield. LTMEO yielded a yellow, aromatic oil with a density of 0.856 g/mL, a refractive index of 1.439, and a yield of 0.60%, consistent with the quality requirements of SNI 9231:2023. GC–MS profiling identified citronellal as the dominant compound, with concentrations of 83.88% in LEO, 69.88% in LTMEO, and 46.47% in TEO. FTIR spectra confirmed the presence of aldehyde functional groups, consistent with the high citronellal content. Minor constituents such as linalool (5.24–8.91%), isopulegol (0.47–2.95%), β-citronellol (2.03–12.22%), and citronellyl acetate (4.28–6.48%) were also detected, potentially affecting citronellal isolation. Overall, the findings highlight C. hystrix DC. leaves as the most promising source of citronellal for industrial applications.